(untitled) (e-Journal of Linguistics, 2023)
Micro, Small and Medium Enterprises are currently becoming one of the concerns and priorities of the Indonesian government. Every Micro, Small and Medium Enterprises (MSME) actor builds a business in a location that is considered to have the potential to generate profits. One type of MSME is a paper printing services. This research is a case study of landscape linguistics with a multimodal approach. This study aims to analyze the representation meaning, interactional meaning and compositional meaning of outdoor signs on paper printing business signboards at the Unika Santu Paulus Ruteng campus building surrounding; in the east, south and west of the campus building. The results showed that all outdoor sign data on the signage were verbal signs supported by several contrasting color backgrounds. The representation meaning of the signboards represents the type of business being run, namely the paper printing services. It is indicated by the two main keywords that appear on every signboard, including the word “print or printing” and “photocopy/copi”. In the aspect of compositional meaning, all the data on the signboards contains informative value. Information is placed in a non-linear text framing position and is not placed sequentially. In the salience aspect, the verbal sign in the form of the business name is placed at the top position and is the most salience element in the sign. Placement and a more salience verbal signs aim to make it easier for viewers to see the place of business as well as show the identity and type of business being run. On the other hand, the use of abbreviations on the signboards of a “startup business” creates confusion if it is not accompanied by clear additional information.